2020
DOI: 10.3389/fphar.2020.551745
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Study of the Protective Effects of Sodium Tanshinone IIA Sulfonate Against Atorvastatin-Induced Cerebral Hemorrhage in Zebrafish: Transcriptome Analysis

Abstract: Hemorrhage stroke is a severe vascular disease of the brain with a high mortality rate in humans. Salvia miltiorrhiza Bunge (Danshen) is a well-known Chinese Materia Medica for treating cerebral vascular and cardiovascular diseases in traditional Chinese medicine. Sodium tanshinone IIA sulfonate (STS) is a water-soluble derivative of tanshinone IIA, which is the main active ingredient of Danshen. In our previous study, we established a zebrafish model of cerebral hemorrhage and found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Yu et al reported similar findings 55 and found that IBD is associated to changes in lipid metabolism and energy metabolic intermediates that occur to match the metabolic demands of intestinal inflammation. Hemoglobin is dependent on chlorophyll and porphyrin metabolisms, 56 while riboflavin metabolism may be related to the production of inflammatory cytokines in IBDs. 57 STV-Na administration significantly changed these metabolic pathways by inhibiting inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al reported similar findings 55 and found that IBD is associated to changes in lipid metabolism and energy metabolic intermediates that occur to match the metabolic demands of intestinal inflammation. Hemoglobin is dependent on chlorophyll and porphyrin metabolisms, 56 while riboflavin metabolism may be related to the production of inflammatory cytokines in IBDs. 57 STV-Na administration significantly changed these metabolic pathways by inhibiting inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Tg (cmlc2: GFP) zebrafish with GFP specifically expressed in myocardial cells were used in this study. Zebrafish were maintained as described in the Zebrafish Handbook ( 28 ). All animal experiments were approved by the Animal Research Ethics Committee of Shanghai University of Traditional Chinese Medicine.…”
Section: Methodsmentioning
confidence: 99%
“…Tanshinone IIA treatment promotes the recovery of brain function and increases neuronal viability; furthermore, the glucose concentration in the serum and cultured medium was increased, possibly regulated by an increased glucose uptake ability and activation of the PI3K/AKT/mTOR pathway ( 19 ). Sodium tanshinone IIA sulfonate is a water-soluble derivative of tanshinone IIA, which suppresses the expression of HIF-1 and hemoglobin genes via inhibition of the PI3K/AKT/mTOR pathway, thereby protecting against hypoxia in cerebral hemorrhage in zebrafish ( 20 ). Catalpol , an iridoid glycoside compound, the main active component of Rehmannia glutinosa Libosch (Di-Huang in Chinese), is commonly used in TCM for treating diseases of aging and stroke ( 21 ).…”
Section: Active Extracts Of Chinese Medicinesmentioning
confidence: 99%
“…The neuroprotection of herbal single components through the PI3K/AKT pathway is detailed in the main text, some herbs contain multiple active components that synergistically protect the nervous system through PI3K/AKT-mediated downstream molecules. There are four active components of Salvia miltiorrhiza, including Sodium tanshinone IIA sulfonate, Sal A, SMND-309, and Cryptotanshinone, exert neuroprotection synergistically through the four PI3K/AKT-mediated pathways, including increasing neuronal viability, preventing apoptosis and promoting neurogenesis ( 20 , 56 , 59 ). Ginkgo biloba has various therapeutic effects, and contains multiple active components, like Ginkgolides, bilobalide, Ginkgetin aglycone.…”
Section: Conclusion and Prospectmentioning
confidence: 99%